2007
DOI: 10.1002/bit.21519
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure inactivation of dried microorganisms

Abstract: Dried microorganisms are particularly resistant to high hydrostatic pressure effects. In this study, the survival of Saccharomyces cerevisiae was studied under pressure applied in different ways. Original processes and devices were purposely developed in our laboratory for long-term pressurization. Dried and wet yeast powders were submitted to high-pressure treatments (100-150 MPa for 24-144 h at 25 degrees C) through liquid media or inert gas. These powders were also pressurized after being vacuum-packed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This effect has already been reported on yeasts, where higher inactivation has been observed at lower water activity. However, inactivation has been observed for fully hydrated yeasts using pressurized nitrogen, but this inactivation was essentially due to the compressive effect rather than a specific gas effect (Espinasse et al, 2008a, b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect has already been reported on yeasts, where higher inactivation has been observed at lower water activity. However, inactivation has been observed for fully hydrated yeasts using pressurized nitrogen, but this inactivation was essentially due to the compressive effect rather than a specific gas effect (Espinasse et al, 2008a, b).…”
Section: Resultsmentioning
confidence: 99%
“…The gas bags were then placed in an hydrostatic press, 1.5 L, operating up to 600 MPa (GEC Alsthom ACB, Nantes, France), to carry out the high pressure experiment. This gas pressurization protocol has been detailed in a previous study (Espinasse et al, 2008a). All the experiments were performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper (Espinasse et al, 2007), we showed for the first time that high pressures of nitrogen were efficient in inactivating dried yeast cells after a treatment of 150 MPa during 24 h whereas the same treatment in a non-aqueous liquid (octadecafluorooctane) without any gas atmosphere had no influence on cell viability. Then, pressurized nitrogen proved to exert specific effects on dried cells, distinct from compression effects observed in octadecafluorooctane.…”
Section: Dynamic Effectsmentioning
confidence: 86%
“…Although yeast is known to survive at very high pressure (Espinasse et al, 2008), little is known about its behavior in contact with high pressure mercury. Therefore X-ray microtomographic investigation of a yeast grain is realized.…”
Section: Introductionmentioning
confidence: 99%